Hubungan Karakteristik Responden Dengan Self Manajemen Pada Pasien Diabetes Mellitus Type 2 Di Poli Penyakit Dalam Rumah Sakit Santa Elisabeth Bantul - Kristanti, Fittriya; Eka Noviati, Bernadetta; Permata Sari, Susan; Zulaika, Umi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Type 2 diabetes mellitus is a metabolic disorder characterized by high levels of glucose in the blood due to impaired insulin secretion or insulin resistance. Macrovascular disorders (eg coronary heart disease) and microvascular disorders (eg retinopathy) are complications that often occur in patients with uncontrolled type 2 DM. Proper treatment to avoid complications requires efforts to be made by type 2 DM patients to control themselves by implementing self-management. Objective: This study aims to determine the relationship between respondent characteristics and self-management of type 2 diabetes mellitus in the internal medicine clinic at Santa Elisabeth Hospital, Bantul. . Methods: This research method is a quantitative descriptive study with a simple survey. The instrument used is the DSMQ (Diabetes Self-Management Questionnaire) questionnaire which is used to measure diabetes self-management. The number of samples in this study was 73 diabetes respondents who met the inclusion and exclusion criteria Results: The results of this study show that education and family history (Type 2 DM) have a p value >0.05. Conclusion: Based on this research, it can be concluded that education and family history (Type 2 DM) significantly influence self-management in Type 2 DM patients. It is hoped that the results of this research can be a guide in making decisions regarding appropriate nursing actions for Type 2 DM patients Keywords: Respondent Characteristics, Self Management, Type 2 Diabetes Mellitus